PT Pelni's Operational Performance as a Livestock Ship Operator - Dignawan Yuwono; Sri Untung; Francis Tantri (Institut Transportasi dan Logistik Trisakti, 2019)
Research aims to determine the achievement of operational performance of ships in aspects of marketing, operations, and finance in the Livestock Transport and Distribution Program. It started from the achievement of the number of livestock, the fulfillment of proper ship facilities, and the achievement of efficient financial value. This research was conducted at PT Pelni (Persero) using descriptive qualitative methods. Data were collected from interviews with 26 related people, observations, documentation, and Focus Group Discussion (FGD) with 8 interested parties. The results of marketing performance analysis show that service product development is return cargo, the image of service products organized by the government, the highest market share acquisition of 23.30% in 2018, and lower tariffs of 25.77% to 48.14% from private operators. Whereas the results of the analysis of operating performance show that OTP has not achieved 3 (three) times in 2018, an eligible tracking system, completed SMC, and animal welfare facilities. Finally, the results of financial performance analysis show that the highest GPM is 8.64% and NPM 7.44%, government subsidies above 80%, and fuel costs above 40% in common-size, and livestock payload income is below the index.